A review on the effectiveness of change management in organization / Robeahtul Nabihah Anamallah and Nurhidayah Hashim. - Anamallah, Robeahtul Nabihah; Hashim, Nurhidayah (Universiti Teknologi MARA Cawangan Selangor, 2018)
In dealing with information is the crucial task in organization which can lead to the information leaking or wrong information. The process in sharing the knowledge during the transformation of work management also important because the change management are build a new and more effective work performance. Hence, change management is important for all organization. In the literature review study, the author highlighted the change management in organization which change leadership, the communication, and employee engagement and employee commitment. The literature review is significant to individual, organization, policy makers and knowledge workers